EVALUATING TOBACCO ADVERTISING VIOLATIONS AND IT’S CONTRIBUTION TO LOCAL REVENUE IN MAKASSAR - Musyarrafah Hamdani; Sri Wahyuni; Ismi Sultan; M. Alimin Maidin; Ahmad Wadi; Hadijah Hasyim; Achmad Mawardi Shabir (The Indonesian Journal of Public Health, 2021)
ABSTRACT Around 50.82% of the age group 15-19 years were smokers in Makassar city, one of which was influenced by tobacco ads exposure (National Institute of Health Research and Development, 2019b). This study aimed to evaluate the violation of tobacco product advertising to Local Regulation of South Sulawesi No. 1 of 2015 on Smoke-Free Area (SFA) in 2019 and its contribution to local revenue of Makassar City in 2018. This was a descriptive study through a quantitative approach with cross sectional design. The observation was conducted on 21 major roads and the document review was performed by processing and analyzing the secondary data of the Regional Revenue Department of Makassar City 2018. Data were analyzed descriptively using IBM SPSS 22. This study found around 51% of 619 tobacco advertising (banner, billboard, name board, poster, pushcart, and video Tron) did not comply with the  Local Regulation of South Sulawesi 1/2015. The violations were located in SFA (2%); near schools and healthcare facilities (14%); cut off the roads (16%); the size >72 m2 (6%); and near government offices (40%). The contribution of tobacco advertising was only IDR 736,643,634,-., which was around 0.02% of the local revenue. The violation of tobacco advertising to the Local Regulation 1/2015 and a very small contribution to local revenue showed that Mayor Regulation on Total Tobacco Advertising, Promotion, and Sponsorship (TAPS) Ban should be carried out immediately to prevent children to be the target tobacco industries in Makassar City.Keywords: tobacco advertising, TAPS contribution, local revenue